Optimizing battery energy storage system for campus micro grid: Economic and environmental benefits of strategic sizing - Iscan, Sercan; Arikan, Oktay (ELSEVIER, 2025)
Optimizing the size of the Battery Energy Storage System (BESS) in campus microgrids (MG) is essential for achieving economic and environmental sustainability. The primary aim of this study is to determine and evaluate the optimal size of the BESS for a campus, taking into account peak load reduction and a carbon trading strategy. Therefore, the system is modeled as a total cost minimization problem under a Time-of-Use (ToU) pricing plan. A Mixed Integer Linear Programming (MILP) approach is applied to five case studies with varying MG configurations and operational strategies. Compared to the base case, the results demonstrate that economic benefits range between 48.87 % and 51.5 %, while COQ emissions are reduced by 0.04 % to 0.078 %, depending on the scenario. Additionally, peak load shaving improvements range from 6.48 % to 15.6 % across the different scenarios. These findings provide practical insights for campus energy management, highlighting the significance of combining cost-effective BESS solutions with peak load shaving and carbon pricing mechanisms.
Keywords: Energy management; Micro grid; BESS sizing; Peak load shaving; Carbon trade; MANAGEMENT; Energy & Fuels